Effect of dehydration on spectral reflectance and photosynthetic efficiency in Umbilicaria arctica and U. hyperborea - M. Barták; K. Trnková; E. S. Hansen; J. Hazdrová; K. Skácelová; J. Hájek; M. Forbelská (Biologia plantarum, 2015)
In many polar and alpine ecosystems, lichens of genus Umbilicaria represent dominant species forming community structure. Photosynthetic and spectral properties of the lichens may change rapidly according to an actual hydration status of their thalli. In this study, we investigated responses of photochemical reflectance index (PRI), normalized difference vegetation index (NDVI), effective quantum yield of photosynthetic efficiency of photosystem (PS) II (ΦPSII), and several photosynthetic parameters derived from fast induction kinetics of chlorophyll fluorescence (OJIP) to controlled dehydration. We used U. arctica and U. hyperborea collected close to Nuuk, Greenland. In both the species, PRI showed a curvilinear increase with dehydration, i.e., a decreasing water potential (Ψw). The increase was apparent within Ψw range of 0 to -10 MPa. The PRI increase was less pronounced in U. arctica than in U. hyperborea. NDVI decreased with a progressive thallus dehydration in both the species, however, throughout Ψw range of 0 to -30 MPa, U. hyperborea had lower NDVI values than U. arctica. The relationship between ΦPSII and Ψw resulted in a typical S curve. A critical Ψw at which photosynthetic processes were fully inhibited was -30 MPa in both the species, however, species-specific differences in the S curve shape were found. Analyses of photosynthetic parameters derived from OJIPs revealed that the absorption of radiation energy and a trapping rate increased with dehydration in active reaction centres of PS II, the number of which decreased with a more pronounced lichen thallus dehydration. It is concluded that U. arctica and U. hyperborea possess effective physiological mechanisms to maintain an effective photosynthesis when partly dehydrated (the Ψw range of 0 to -15 MPa). In spite of similar ecological niches that these two lichens occupy in nature, their spectral and photosynthetic properties differred.